A6.1 "Intratracheal inoculation of porphyromonas gingivalis induces inflammatory changes in the joints of DBA/1 mice". (31st January 2014) - Adamowicz, Karina; Maresz, Katarzyna; Benedyk, Małgorzata; Hellvard, Annelie; Mydel, Piotr; Potempa, Jan
Abstract : Background: Rheumatoid arthritis (RA) is a systemic autoimmune disease manifested by chronic inflammatory disorder of the joints. The recent clinical and epidemiological studies provided strong evidence for a significant association between RA and periodontitis (PD). Moreover, our findings shown that Porphyromonas gingivalis, the major etiologic factor in PD, facilitates the development and progression of collagen induced arthritis. Objective: The purpose of the study was to establish whether P. gingivalis alone might directly cause inflammatory changes of the joints of infected animals and dependence of this pathological event on the administration route of the bacterium and a genetic background of mice. Methods: DBA/1, C57BL/6, and BALB/c mice were infected with P. gingivalis (5x10 7 ) using different routes of administration: intratracheal, intravascular, intraperitoneal, oral and intra-subcutaneous. After 14 days, the clinical score measurement of mice paws, physiological parameters and host response to infection were taken. Arthritis was quantified by clinical score measurement of ankle swelling in the paws and by histological examination. Inflammatory response was evaluated by determination of proinflammatory cytokines in serum using ELISA. Dissemination of P. gingivalis to paws and organs was determined by plating tissue homogenates on blood agar and CFU count. Finally, the presence or absence of P. gingivalis in the inflamed joint tissue was verified using PCR to specifically detect 16S RNA of P. gingivalis . Results: Intratracheal infection with 5x10 7 P. gingivalis did not lead to systemic infection and live bacteria were eliminated twenty-four hours postinfection from the lungs. Moreover, no live bacteria were found in other organs and blood at any time after bacterial administration. However, significant ankle swelling occurred in DBA/1 mice 7 days after P. gingivalis challenge. In contrast to DBA/1, BALB/c and C57BL/6 mice were resistant to joint inflammation generated by P. gingivalis intratracheal infection. The arthritic joints in DBA/1 mice exhibited inflammatory changes in synovial tissue. Serum proinflammatory mediators such as IL-6, TNF-alpha, IL-10, MCP-1 were found to be elevated one week after infection, which correlated with the onset of inflammatory changes in the joints. Other routes of P. gingivalis administration did not lead to inflammatory changes in the joints. Conclusion: Intratracheal infection is the first animal model that directly links P. gingivalis to changes in the joints and shows that the bacterium may play a crucial role in the pathogenesis of periodontitis-associated rheumatoid arthritis in susceptible genetic background.